Depression, suicidality, substance-use and associated factors among people living with HIV the COVID-19 pandemic in Uganda - Rukundo, Godfrey Zari; Wakida, Edith K.; Karungi, Christine K.; Asasira, Jenipher; Kumakech, Edward; Obua, Celestino (Plos one, 2023)
Background: Mental disorders are common in people living with HIV (PLHIV) but they are often unrecognized and untreated. Furthermore, the COVID-19 pandemic has disrupted the already limited mental health services in low resource countries such as Uganda, and yet the extent to which the COVID-19 mitigation measures have affected the mental health of PLHIV is not fully known. We aimed to determine the burden of depression, suicidality, substance use and associated factors among adult PLHIV who were seeking care at two HIV clinics in northern and southwestern Uganda. Methods: We conducted a phenomenological qualitative and quantitative cross-sectional study among 431 PLHIV to determine the burden of depression, suicidality and substance-use disorders at two HIV clinics, at Lira Regional Referral Hospital and Mbarara Regional Referral Hospital in northern and southwestern Uganda respectively, during the COVID-19 lockdown. We used the Patient Health Questionnaire (PHQ-9) to assess for depression and suicidality, and the Michigan Assessment-Screening Test for Alcohol and drugs (MAST-AD) to assess for substance use disorder. We conducted descriptive statistics analysis to determine the burden of the disorders, and logistic regression to determine the associated factors. For the qualitative method we conducted in-depth interviews with 30 PLHIV and did thematic analysis. Results: Of the 431 PLHIV surveyed, mean age was 40.31 ± 12.20 years; 53.1% (n = 229) had depression; 22.0% (n = 95) had suicidality; and 15.1% (n = 65) had substance-use disorder. Female gender (PR = 1.073, 95%CI 1.004–1.148, P = 0.038), lack of formal education (PR = 1.197, 95% CI 1.057–1.357, P = 0.005), substance-use disorder (PR = 0.924, 95%CI 0.859–0.994, P = 0.034) and suicidality (PR = 0.757, 95%CI 0.722–0.794, p = 0.000) were associated with depression after adjusting for confounders. Further analysis showed that being female (PR = 0.843, 95% CI 0.787–0.903, P = 0.000*) and having depression (PR = 0.927, 95% CI 0.876–0.981, P = 0.009) and owning a large business (PR = 0.886, 95% CI 0.834–0.941, p = 0.000*) were significantly associated with having a substance-use disorder. Only depression was independently associated with suicidality after adjusting for confounding factors (PR 0.108, 95%CI 0.054–0.218, p = 0.000*). For the qualitative results, there were three apriori themes: a) Burden of depression, b) substance-use, and c) suicidality among the PLHIV during the COVID-19 containment measures. Conclusion: There was high prevalence of depression, suicidality and substance-use disorder in adult PLHIV in Uganda during the COVID-19 pandemic and the associated lockdown measures. The three mental health problems seem to have bidirectional relationships and gender has a lot of contribution to the relationships. Interventions aimed at any of the disorders should consider these bidirectional relationships.
Keywords: Depression; Suicidality; COVID-19; Uganda; Mental disorders; HIV